Rendahnya Konsentrasi Peserta Didik dalam Proses Pembelajaran - Riris Setyasa Hermawati; Artika Chrissa Agustina; Dina Nur Evitasari; Devlina Fatimah Munandar; Sri Suwartini (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Concentration is a crucial aspect of the learning process, playing a significant role in students' success in understanding subject matter. Low levels of concentration can hinder information acquisition, decrease motivation, and negatively impact learning outcomes. This paper aims to identify factors influencing low student concentration, analyze their impact on material comprehension, and examine effective learning strategies to improve student concentration. Factors affecting concentration can be divided into two categories: internal factors such as health, interests, talents, and motivation, and external factors such as family circumstances, the school environment, and the community. The impacts of low concentration include difficulty understanding material, decreased critical thinking skills, and decreased motivation and self-confidence. To address these issues, educators need to implement varied and engaging learning strategies, such as the use of icebreakers and role-playing methods, to create a fun classroom atmosphere and support the achievement of optimal learning outcomes.